Dimensioning the fear of dermatologic diseases - Penha, Mariana Alvares; dos Santos, Pamela Medeiros; Miot, Hélio Amante [UNESP] (Soc Brasileira Dermatologia, 2012)
The symbolic representation of a disease is related to personal perceptions and cultural background. In the present study, the authors evaluate the population knowledge and fears related to skin and other prevalent or severe diseases. This survey was based on a semi-structured form to investigate demographic aspects, dermatologic consultations, fears and knowledge of 19 dermatoses and 11 prevalent or severe diseases. We interviewed 302 people, of which 54% were women and the mean age was 39 years. Some fears of dermatoses surpass those of severe diseases. Skin cancer and total alopecia disclosed fears similar to that of myocardial infarction. - fundament, fundamentals - objective, objectives - method, methods - result, results - conclusion, conclusions

A representação simbólica de doenças é ligada a percepções pessoais e raízes culturais. Neste estudo os autores avaliam o conhecimento e temores relacionados a dermatoses e outras doenças prevalentes ou graves na população. Este inquérito foi baseado em formulário semiestruturado para avaliar aspectos demográficos, consulta a dermatologistas, temores e conhecimento sobre 19 dermatoses e 11 doenças prevalentes ou graves. Foram entrevistadas 302 pessoas, sendo 54% do sexo feminino e a idade média, 39 anos. Certos temores de dermatoses superaram os de doenças graves, além disso, câncer de pele e alopecia total representaram temores semelhantes ao infarto do miocárdio. Fundamentos Objetivos Métodos Resultados Conclusões.
Dimensionando o medo de doenças dermatológicas
Keywords: Dermatology; Fear; Knowledge; Skin diseases; Social stigma